Attitudes of healthcare workers and members of the public toward the COVID-19 vaccine: A cross-sectional survey - Shira Ramot; Orna Tal (Taylor & Francis Group, 2022)
The COVID-19 pandemic has led to the rapid development and implementation of vaccines. However, uncertainty about their safety and effectiveness among some people has led to vaccine hesitancy. We conducted a cross-sectional survey in March 2021 among individuals from the general Israeli population and health-care workers (HCWs) to examine risk perception toward the COVID-19 vaccine, trust in health-care providers and information sources used for making health-related decisions. The study population included 739 respondents: 42.6% HCWs and 57.4% members of the public. Participants' perceived risk toward the vaccine was relatively low in both populations. Higher perceived benefit of the vaccine, higher perceived extent of knowledge that doctors have about the risk associated with the vaccine, higher perceived freedom to choose whether to get vaccinated and higher trust in health-care providers predicted lower perceived risk toward the vaccine. Individuals who showed greater health responsibility, those who usually get vaccinated against influenza and those who had greater objective knowledge on the COVID-19 vaccine demonstrated lower perceived risk. No statistically significant difference in trust level was found between HCWs and members of the public. Both populations regarded information from medical sources as their greatest influence on health-related decisions. The study points to the factors influencing the perceived risk toward the COVID-19 vaccine and emphasizes the unique status of HCWs having their own views and concerns about the vaccine as individual members. Policymakers should consider these factors when planning national vaccination campaigns.